Knowledge and attitude of medical students towards autopsy - Sharmila Gurung; Biplab Manandhar; Shalini Bhakta (Janaki Medical College Journal of Medical Science, 2025)
Background & Objectives: Autopsies are important to medical practice and training due to its significant implications for medical education and legal procedure. Consideration of existing trends in autopsy practice requires insight into the perceptions and attitudes of one of the key stakeholders—especially medical students, who represent the future of medical practice. Thus, this study aims to assess their knowledge and attitudes regarding current autopsy practices.Material and Methods: This was a cross-sectional descriptive study conducted on MBBS students of Devdaha Medical College. A structured questionnaire was used to collect data on the knowledge and attitude of the students towards autopsy using the 1-5 Likert scale. The data was entered into Excel sheet and represented in percentage and frequency.Results: A substantial proportion (75.3%, 48%, 61.4%) strongly agreed that autopsies are legal formalities, primarily conducted in unnatural deaths, with removal of viscera for histopathological and toxicological analysis, respectively. Furthermore, 46% and 51.4% acknowledged the importance of both external and internal examinations following legal documentation. However, indecision was noted regarding specific procedural details such as the use of preservatives (38.7% neutral) and issuance of death certificates in “brought dead” cases (32.7% neutral). Most students felt comfortable witnessing autopsy (56%) and the need to observe more (36%). Some perceived autopsy to be disrespectful 40.7% while 40% remained neutral. Many strongly disagreed to parting autopsy demonstrations from the curriculum (34%) and independently doing autopsies (40%). Most of them preferred both traditional and virtual (38.7%) method of autopsy.Conclusion: Most students viewed autopsies as essential legal procedures and supported continued exposure through both traditional and virtual methods. However, some were unsure about specific practices, and opinions were divided on the dignity of the process.